EFFORTS TO BUILD GLOBAL AWARENESS THROUGH SOCIAL STUDIES LEARNING IN THE ERA OF INDUSTRIAL REVOLUTION 5.0 - Fatmawati, Emiliya; Ningsih, Tutuk (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2024)
In the era of Industrial Revolution 5.0, it is important to understand how social studies learning can build global awareness in students. This article explores the challenges and opportunities in implementing social studies learning in this changing era. Key challenges include technology integration, cultural diversity and understanding complex global issues. However, there are significant opportunities in the use of technology, project-based learning and the development of 21st century skills in social studies learning. The purpose of this study is to investigate how practical approaches in social studies learning can help build global awareness in students in the era of Industrial Revolution 5.0. The results showed that the integration of technology, project-based approach, and 21st century skills development significantly improved the effectiveness of social studies learning in building global awareness. The practical implementation of these strategies opens up opportunities to prepare students to be adaptive global citizens, responsive to change, and contribute to the development of a more sustainable world. In conclusion, social studies learning in the era of the Industrial Revolution 5.0 has great potential to be a driving force in shaping a generation that has a strong global awareness and is ready to face complex global challenges.Keywords: Challenges and opportunities; Global awareness; Industrial revolution 5.0; Social studies learning;